Технологічні параметри інтенсивного пророщування зерна для годівлі птиці - Гавдида, Г. І.; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym; Ломейко, Олександр Петрович; Ломейко, Александр Петрович; Lomeiko, Oleksandr (Мелітополь: ТДАТУ, 2021)
UK: Робота присвячена дослідженню процесу інтенсивного пророщування зерна для годівлі птиці з визначенням впливу технологічних параметрів: тривалості пророщення, розташування зерна в шарі солоду і експозиції іонізації повітря на швидкість його пророщування. Цей процес статистично значуще залежить від усіх досліджуваних факторів, а отримана дисперсійна модель на 95,1 % описує досліджуваний процес. Залежність інтенсивності пророщування зерна від тривалості його пророщування пояснює 98,3 % експериментальних точок, а від експозиції іонізації логарифмічної функції пояснює 98,7 % точок. RU: Работа посвящена исследованию процесса интенсивного проращивания зерна для кормления птицы с определением влияния технологических параметров: длительности проращивания, расположение зерна в слое солода и экспозиции ионизации воздуха на скорость его проращивания. Этот процесс статистически значимо зависит от всех исследуемых факторов, а полученная дисперсионная модель на 95,1% описывает исследуемый процесс. Зависимость интенсивности проращивания зерна от продолжительности его проращивания объясняет 98,3% экспериментальных точек, а от экспозиции ионизации логарифмической функции объясняет 98,7% точек. EN: The work is sanctified to research of process of the intensive sprouting of grain for feeding of bird with determination of influence of technological parameters. Most effective way of upgrading of production of stock-raising goods, in particular, organically clean, consists in the increase of production of quality forage volumes. One of methods of decision of this task there is the use of grain, that can be basis of receipt organically of clean products at growing of bird. Therefore intensification of process of sprouting of grain with the aim of receipt of valuable feed material is an actual task on the modern stage of development of the poultry farming Aim of this work is determination of influence of the most meaningful factors on intensity of sprouting of grain. The basic technological parameters of this process are: duration of sprouting, location of grain in the layer of material and display of ionising of air. Dependence of intensities of sprouting of grain from duration of his sprouting are explained by 98,3 % experimental points, and from the display of ionising of logarithmic function of 98,7 % points. The increase of intensity of sprouting of grain from duration of process is explained by that the increase of length of sprouts causes the increase of intensity of breathing of vegetable material and height of temperature in the layer of malt that improves the terms of height of sprouts. Present substantial difference between the size of sprouting of grain at be to what duration of ionising of air and her absence explained by the insufficient interval. of varying of ionising display.
Технологические параметры інтенсивного проращивания зерна для кормления птицы
Technological parameters of intensive sprouting of grain are for feeding of bird
Keywords: експозиція іонізації повітря; інтенсивність пророщування зерна; тривалість пророщування; логарифмічна функція; досліджувані фактори; технологічні параметри; розташування зерна; экспозиция ионизации воздуха; интенсивность проращивания зерна; продолжительность проращивания; исследуемые факторы; технологические параметры; расположение зерна; are a display of ionising of air; intensity of sprouting of grain; sprouting duration; logarithmic function; prospected factors; technological parameters; locations of grain